Redox responses in patients with sepsis: high correlation of Thioredoxin-1 and macrophage migration inhibitory factor plasma levels - Brenner, Thorsten; Rosenhagen, Claudia; Steppan, Jochen; Lichtenstern, Christoph; Weitz, Jürgen; Bruckner, Thomas; Martin, Eike; Hoffmann, Ursula; Weigand, Markus A.; Hofer, Stefan (Mediators of inflammation, 2010)
Background. Redox active substances (e.g., Thioredoxin-1, Macrophage Migration Inhibitory Factor) seem to be central hubs in the septic inflammatory process. Materials and Methods. Blood samples from patients with severe sepsis or septic shock ( ) were collected at the time of sepsis diagnosis (t0), and 24 (t24) and 48 (t48) hours later; samples from healthy volunteers ( ) were collected once; samples from postoperative patients ( ) were taken one time immediately after surgery. In all patients, we measured plasma levels of IL-6, TRX1 and MIF. Results. The plasma levels of MIF and TRX1 were significantly elevated in patients with severe sepsis or septic shock. Furthermore, TRX1 and MIF plasma levels showed a strong correlation (t0: : ). Conclusions. Proinflammatory/~oxidative and anti-inflammatory/~oxidative agents show a high correlation in order to maintain a redox homeostasis and to avoid the harmful effects of an excessive inflammatory/oxidative response.
Gesehen am 24.02.2023